2020
DOI: 10.1007/s00467-019-04360-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism disorders in children with refractory nephrotic syndrome

Abstract: Background: Patients with refractory nephrotic syndrome (NS) are at high risk of medication-induced glucose metabolism disorders, because of their long-term use of diabetogenic medications, particularly glucocorticoids and calcineurin inhibitors (CNIs). However, there have been no comprehensive evaluations of glucose metabolism disorders in pediatric patients with refractory NS. Moreover, glucocorticoids and CNIs could not be discontinued in these patients until the effectiveness of rituximab on refractory NS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Though, the results demonstrated a notably elevated prevalence rate of IR in overweight and generally obese children [17,23]. The same results were obtained by T. Takahashi et al [24] that obese/overweight patients had significantly more glucose metabolism disorders than non-obese/non-overweight once. IR is usually one of the first metabolic damage diagnosed in obese children and the key risk factor for the development of comorbidities [25].…”
Section: Discussionsupporting
confidence: 58%
“…Though, the results demonstrated a notably elevated prevalence rate of IR in overweight and generally obese children [17,23]. The same results were obtained by T. Takahashi et al [24] that obese/overweight patients had significantly more glucose metabolism disorders than non-obese/non-overweight once. IR is usually one of the first metabolic damage diagnosed in obese children and the key risk factor for the development of comorbidities [25].…”
Section: Discussionsupporting
confidence: 58%
“…The OGTT should not be neglected, because evidence from studies on DM2 in adults shows that not performing an OGTT could lead to underdiagnosis of diabetes [ 24 ]. Furthermore, a study on children treated with steroids and CNIs because of the refractory NS showed that 40% of all glucose homeostasis disturbances were diagnosed only by the 2-hour OGTT [ 6 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, it is generally considered that if the treatment does not damage the pancreatic β-cells in an irreversible way, the severity of glucose homeostasis impairment should be reduced partially (to pre-diabetes state) or totally (to euglycaemia) after the drug discontinuation. Research performed on a small group showed that the pre-diabetes states persisted in 71% of children with nephrotic syndrome (NS) treated with steroids and calcineurin inhibitors (CNIs) [ 6 ]. The series of case reports on a similar group indicates only a transient glucose metabolism disturbance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids remain the mainstream of treatment for INS after excluding the possible secondary factors and have obtained excellent results in improving survival of both patients and kidney function [ 10 ]. However, patients with refractory INS are at high risk of medication-induced glucose metabolism disorders, such as diabetes [ 11 , 12 ]. The prevalence of steroid-induced diabetes mellitus (SIDM) in INS was 6.2% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%